Pengaruh Kompetensi, Motivasi Berprestasi dan Disiplin Terhadap Kinerja Guru SMA Muhammadiyah 1 Karanganyar - Ratnasari, Ninik; Fii Ahsani, Riska (Teewan Journal Solutions, 2025)
Waroeng The phenomenon of this study, the less than optimal performance of teachers at SMA Muhammadiyah 1 Karanganyar, is marked by a decline in the results of the 2023 teacher performance assessment (PKG) compared to the previous year. The purpose of this study is to analyze the significance of the influence of competence on teacher performance at SMA Muhammadiyah 1 Karanganyar, to analyze the significance of the influence of achievement motivation on teacher performance at SMA Muhammadiyah 1 Karanganyar, to analyze the significance of the influence of discipline on teacher performance at SMA Muhammadiyah 1 Karanganyar. The population of this study was all teachers at SMA Muhammadiyah 1 Karanganyar with a total of 56 people. This study used saturated sampling, namely taking all members of the population as samples. The data collection technique used a questionnaire assessed on a 5-point Likert scale. The data analysis technique used multiple linear regression analysis. The results of the analysis show that (1) Competence has a significant effect on the performance of teachers at SMA Muhammadiyah 1 Karanganyar as indicated by the p value (0.007) <0.05, thus hypothesis 1 is proven. (2) Achievement motivation has a significant effect on the performance of teachers at SMA Muhammadiyah 1 Karanganyar, as shown by p value (0.021) < 0.05, thus hypothesis 2 is proven. (3) Discipline has a significant effect on the performance of teachers at SMA Muhammadiyah 1 Karanganyar, as shown by p value (0.000) < 0.05, thus hypothesis 3 is proven.